PROFESSIONALLY ORIENTED ENGLISH TEACHING TO STUDENTSPHILOLOGIST (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2024)
The article outlines some areas of professionally oriented teaching of English on the example of philologists. The main goals and objectives of the article are formulated. The relevance of the issue under consideration is indicated. The author emphasizes that the leading method in teaching professionally oriented English is the communicative method. In theoretical and methodological terms, this problem has not been fully studied, today many researchers and scientists are working on it. Some areas of providing professionally-oriented teaching of English to bachelors of philology are highlighted. The author refers to them: studying the needs of society in philological education, changing the content of education, which should contribute to the formation of communicative and professional competencies, as well as the creation of an educational and methodological base for the learning process.